D4.4 Material from 1st workshop - Hadjimitsis, Diofantos G.; Nisantzi, Argyro; Lysandrou, Vasiliki; Agapiou, Athos; Themistocleous, Kyriacos (My University, 2016)
The specific deliverable summarizes the material related to the first workshop of the project entitled as 'Copernicus Contribution to Cultural Heritage'. This include actions prior to the workshop, such as the agenda prepared, as well as material deriving from the workshop per se (such as the presentations that took place), the list of participants etc.
Keywords: Copernicus; Cultural heritage